Board of directors characteristics, supervisory board and China listed financial fraud companies - Meihui, Du (2024)
This paper aimed to study the factors affecting financial fraud in listed companies to help investors effectively prevent major losses caused by corporate fraud, and to provide a basis for regulatory and legislative bodies to improve relevant controls. More importantly, it aimed to alert listed companies to the seriousness of the problem of financial fraud in order to improve financial reporting quality. This study involved an empirical analysis of the relationship between certain governance characteristics and financial fraud in Chinese listed companies from 2018 to 2022. The research design comprised descriptive analysis, correlation analysis and regression analysis of 50 companies that committed financial fraud and 50 companies that did not commit fraud. The empirical results showed that the size of the board of directors and the shareholding ratio of the largest shareholder were significantly negatively correlated with financial fraud, while the proportion of independent directors, CEO duality, the financial professional background of the members of the board of supervisors, and the size of the board of supervisors were not significantly associated with financial fraud